Oral health, oral follow-up and infectious risk management of rheumatoid arthritis patients on anti-TNF drugs: a survey of a French e-cohort - Loredana Radoi; Hubert Marotte; Adelyne Ruyssen-Witrand; Martin Soubrier; Sonia Trope; Naïma Hamamouche; Raphaele Seror; Marjolaine Gosset (BMC Oral Health, 2026)
Abstract Background As periodontitis is a recognized risk factor for rheumatoid arthritis (RA), it should be adequately treated before the initiation of biologic disease-modifying antirheumatic drugs (bDMARDs), along with any concomitant acute oral infection. bDMARDs remains a concern for patients, and can pose challenges for dentists, particularly regarding the management of invasive procedures. Our aim was to assess adherence to oral health recommendations, and perioperative management of invasive dental procedures in RA patients with bDMARDs. Methods A French online cross-sectional survey was conducted within the ART e-cohort. A semi-structured 77-item questionnaire was developed by a multidisciplinary team (rheumatologists, dentists, expert patients). Validated oral health scores (Oral Health Impact Profile [OHIP-14] and Periodontal Screening Score [PESS]) were calculated from responses and combined with routine cohort data (RAPID-3, EQ-5D-5 L). Results Of 543 e-cohort participants, 279 completed the survey (response rate 51.4%; 71% female; 70% aged ≥ 50 years). RA duration exceeded 5 years in 63.7%. Most participants (90%) were receiving bDMARD, including 67% on anti-TNF. Moderate-to-severe RA activity was common (53% with RAPID-3 ≥ 7). The mean EQ-5D-5 L index was 0.605. Based on a PESS > 5 41.6% of respondents were identified at risk of severe periodontitis. The risk increased with age, smoking, alcohol consumption, and RA severity, but was not associated with treatment type. Only 16.5% of participants fully adhered to French professional oral health recommendations, including twice-daily tooth brushing, interdental cleaning and annual dental check-ups). One in four patients had undergone invasive dental procedures within 2 years; 68.5% continued bDMARD therapy. Post-operative complications were rare, all after extractions without antibiotic cover. Conclusions In the present cohort, RA patients showed low adherence to oral health recommendations and high risk of severe periodontitis. Postoperative complications while continuing bDMARDs were infrequent.